Non‐isothermal Crystallization Kinetics of Biobased Poly(ethylene 2, 5‐furandicarboxylate) Synthesized via the Direct Esterification Process. Issue 21 (25th August 2014) - Codou, Amandine; Guigo, Nathanael; van Berkel, Jesper; de Jong, Ed; Sbirrazzuoli, Nicolas
<x xml:space="preserve">Abstract</x> Poly(ethylene 2, 5‐furandicarboxylate) (PEF) is an emergent biobased polyester whose chemical structure is analogous to poly(ethylene terephthalate). Pilot‐scale PEF is synthesized through the direct esterification process from 2, 5‐furandicarboxylic acid and bio‐ethylene glycol. Wide‐angle X‐ray diffraction (WAXD) measurements reveal similar crystallinities and unit cell structures for melt‐crystallized and glass‐crystallized samples. The non‐isothermal crystallization of PEF sample is investigated by means of DSC experiments both from the glass and the melt. The temperature dependence of the effective activation energy of the growth rate is obtained from these data, and the results show that the glass and early stage of the melt crystallization share common dynamics. Hoffman–Lauritzen parameters and the temperature at maximum crystallization rate are evaluated. It is found that the melt‐crystallization kinetics undergo a transition from regime I to II; however, the crystal growth rate from the melt shows an atypical depression at T < 171 °C compared with the predicted Hoffman–Lauritzen theory. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>